26 Investigating Noise Exposure to Newborn Infants with Respiratory Support: Methodological Considerations. (21st October 2022) - Singh, Devika; Fusch, Gerhard
Abstract: Background: Excessive noise in the NICU may lead to serious long-term effects on hearing impairment and sensory development in newborns. As such, the maximum recommended noise level is 45 dBA. Reported studies regarding noise exposure of ventilated preterm infants show inconsistent results; however, these studies also vary considerably in their methodology in terms of noise ascertainment (Table 1). We hypothesize that the study methodology significantly influenced data quality. Objectives: Our aim is to investigate if measured ventilator noise levels from previous literature could potentially be the result of methodological shortfalls of the study design rather than perceivable noise levels. Design/Methods: A ventilator circuit was set up using nCPAP and high frequency mode with nasal prongs. Noise levels were measured using a commercially calibrated noise meter. Three different scenarios were tested. (1) Measurements were taken at different angles of (0°to 180°), with 180° facing the end of the nasal prongs, without a mannequin, with the membrane/orifice of the noise meter placed 2 mm laterally from the prongs. (2) Noise levels were measured at 180° at distances of 0 to 20 mm from the nasal prongs. (3) Measurements were taken in the oral cavity of a life-size intubation mannequin of a newborn baby. Results: Overall, the noise levels produced at different settings varied significantly, ranging from 45.7 dB to 82.2 dB. The average environmental background noise was 44.4 dB. Noise levels typically increased as the angle increased, with the highest noise level at 180° for both high frequency and nCPAP mode, at 58.4 dB and 58.2 dB, respectively (Figure 1). Noise levels recorded at high frequency were slightly higher than nCPAP values. Furthermore, in regards to distance, the highest mean value, 82.2 dB was recorded with the noise meter approximately 3 mm from the nasal prongs, with the lowest mean value, 47.6 dB, being recorded at 20 mm. During trials with the mannequin, the lowest value, 50.1 dB, was recorded at the entrance of the mouth with slightly higher values being recorded within the oral cavity. Conclusion: The results indicate that small changes in experimental settings, such as positioning and distance from the nasal prongs, can greatly influence noise levels, particularly above the recommended levels for neonates. In summary, some study results are potentially influenced more by the study design than the device type or ventilator setting. Further research and detailed reporting in the NICU is recommended.